2011
DOI: 10.1089/cyber.2010.0377
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Facebook So Successful? Psychophysiological Measures Describe a Core Flow State While Using Facebook

Abstract: People are more and more using social networking sites (SNSs) like Facebook and MySpace to engage with others. The use of SNSs can have both positive and negative effect on the individual; however, the increasing use of SNSs might reveal that people look for SNSs because they have a positive experience when they use them. Few studies have tried to identify which particular aspects of the social networking experience make SNSs so successful. In this study we focus on the affective experience evoked by SNSs. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
140
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(159 citation statements)
references
References 33 publications
7
140
1
7
Order By: Relevance
“…First, the time young people spend on SM may actually encroach on the time that is available to sleep, this is the time displacement hypothesis (Cain & Gradisar, 2010). Second, SM use is known to increase arousal (Cain & Gradisar, 2010;Mauri, Cipresso, Balgera, Villamira, & Riva, 2011). For example, Mauri and colleagues (2011) found that during Facebook use participants showed high physiological arousal.…”
mentioning
confidence: 99%
“…First, the time young people spend on SM may actually encroach on the time that is available to sleep, this is the time displacement hypothesis (Cain & Gradisar, 2010). Second, SM use is known to increase arousal (Cain & Gradisar, 2010;Mauri, Cipresso, Balgera, Villamira, & Riva, 2011). For example, Mauri and colleagues (2011) found that during Facebook use participants showed high physiological arousal.…”
mentioning
confidence: 99%
“…Facebook is more socializing then "internet" since it apparently gives an "intense engagement and emotional enjoyment" (Magid, 2012;Mauri, Cipresso, Balgera, Villamira & Riva, 2011). After all, there is a truth in an observation that "Indonesians are a very social and 'chatty'" people (Pramuadji, 2014).…”
Section: Cyberspace and Young Peoplementioning
confidence: 99%
“…Youth culture is perceived as the culture that cultivates experimentation, creativity, playfulness, and adventure (Fraser&Dutta, 2008;Magid, 2012;Mauri, Cipresso, Balgera, Villamira & Riva, 2011).…”
Section: Cyberspace and Young Peoplementioning
confidence: 99%
“…These physiological measures include cardiovascular (heart rate, heart rate variability, blood volume pulse), electrodermal (galvanic skin response), electro-encephalography, electromyography, and respiratory data, to name a few [22,26]. The insights garnered from this physiological data can be used to design more effective systems, create adaptive systems, and help users make more informed decisions [23,34].…”
Section: Introductionmentioning
confidence: 99%